Faktor-faktor yang mempengaruhi tenaga kerja dan produk domestik regonal bruto di kota samarinda - Hidayat, Wahyu; Militina, Theresia; Ulfah, Yana (Faculty of Economics and Business Mulawarman University, 2016)
This research is aim to find out and examine the influence of investment, infrastructure, and wage rate toward manpower and GDRP in Samarinda City. Data used in this research is secondary data processing of taken spanning year time on 2005-2014. Analysis tool used is path analysis. Software used to conduct analyze is SPSS 23 Version. Result of research indicate that in influencing manpower, investment influential directly and insignificant with effect value -0,316 and significance value 0,229 > 0,10, infrastructure influential directly and insignificant with effect value -0,203 and significance value 0,125 > 0,10, and wage rate influential directly and significant with effect value 1,153 and significance value 0,003 < 0,10. In influencing GDRP, investment influential directly and significant with effect value of 0,226 and significance value 0,095 < 0,10, infrastructure influential directly and insignificant with effect value 0,068 and significance value 0,475 > 0,10, manpower influential directly and significant with effect value 0,834 and significance value 0,001 < 0,10. In influencing GDRP through manpower, investment influential indirectly and insignificant with effect value -0,263544, infrastructure influential indirectly and insignificant with effect value -0,169302, and wage rate influential indirectly and significant with effect value 0,961602.Keywords: Investment, Infrastructure, Wage Rate, Manpower, GDRP